Features of Paradigm for forming anti-cataclysmic instruments for preventing aggressive interstate conflicts – artificial intelligence (AI) in terms of ensuring objective personnel evaluation and making objective, humane managerial decisions - B. M. Andrushkiv; L. S. Golovkova; N. B. Kyrych; O. B. Pohajdak; K. Hannouf (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет)
The relevance of the research lies in identifying shortcomings in the field of management of interstate relations and determining the factors that trigger aggressive manifestations within them. Based on the analysis of literary sources and existing experience, the causes of their occurrence have been determined, and ways and means of prevention have been proposed, including the use of artificial intelligence (AI). The article shows that in the context of the Ukrainian military economy, one of the main factors of efficiency of defence work, production and social development is the managerial tools and high-quality personnel which currently being formed in the sectoral and territorial areas, as well as humanism and scientific validity of managerial decisions in the field of interstate partnership relations. It has been established that in these circumstances, AI is not always used effectively, in particular in preventing the emergence of such negative phenomena as corruption and bribery, incompetence and irresponsibility, which are factors of ineffective management and implementation of the state defence policy. Meanwhile, addressing this issue is an urgent need of Ukrainian society and the most important prerequisite for strengthening the state, enhancing its defense positions in the context of preparation for membership in EU and NATO. The authors propose a paradigm of forming an AI-based anti-cataclysmic toolkit for preventing aggressive interstate conflicts initiated by “worthless” leaders. It is proposed to increase the effectiveness of these measures through managerial, state innovation and management mechanisms. The authors argues that the introduction of AI can ensure not only the purity and high quality of managerial personnel, but also use the means for humanitarian selection of applicant members, for example, to the UN, strengthening administrative discipline and organising control over the implementation of decisions in this structure. By improving the management of these factors at the local level, it is possible to ensure not only the appropriate quality of managerial decisions and prevention of abuse, but also peace in society and stable functioning of national economies, which can make them competitive in the EU.